Hak dan Kewajiban dalam Hukum Mawaris: Perspektif Hukum Islam dan Perdata - Ramadhan, Alif Dzaky; Anjelie, Friska; Kurniati, Endah; Nazuro, Zahrotun; Syamsiah, Syamsiah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
Inheritance law is one part of civil law as a whole and is part of family law. The law of inheritance is very closely related to the scope of human life, because every human being will definitely experience a legal event in the form of death. The legal consequences that subsequently arise with the occurrence of a person's death legal event, including how to manage and continue the rights and obligations of a person who has passed away. In the inheritance law, it has been determined who is the heir, and who is entitled to get the share of the inheritance, how much is their share, how the provisions for its division are, and various matters related to the distribution of inheritance are also regulated. The law of inheritance is a law that regulates the transfer of property and material rights from an individual who has passed away to his heirs in accordance with Islamic law.